Organización Contable en el Comercial “Keilita” del Señor Azuero Bravo Bienvenido Olmedo del Cantón Huaquillas, periodo del 01 de Abril al 30 de Junio del 2024. - Agurto Suárez, Jenniffer Dayana (2024)
The Curricular Integration Work was carried out based on the accounting process titled "Accounting Organization in the Commercial 'Keilita' of Mr. Azuero Bravo Bienvenido Olmedo from Huaquillas Canton, from April 1 to June 30, 2024," which was executed to understand the economic and financial situation. The work has a mixed approach as it is both qualitative and quantitative, and various methods and techniques were applied to achieve each of the proposed objectives. Therefore, firstly, the Plan and Chart of Accounts were prepared according to the needs and nature, grouped into: Assets, Liabilities, Equity, Income, Costs, Expenses, and Order Accounts. Subsequently, the accounting process began with the Initial Inventory, using physical verification to determine the real existence and verify the assets, values, rights, and obligations, which led to the preparation of the Initial Balance Sheet. Additionally, all source documentation was collected to chronologically and orderly record each transaction in the Journal with the support of auxiliary records. This facilitated the preparation of the Ledger and then the Trial Balance. The Worksheet was then developed to create the Financial Statements, such as the Statement of Financial Position, which showed that the commercial entity has very high assets amounting to $454,581.07, Liabilities of $13.416,24, and Equity of $441,164.83. In the case of the Income Statement, a significant loss was obtained due to low income that has negatively affected the commercial entity, resulting in a value of $- 9.940,52. Finally, the work concluded by meeting the objectives, establishing that the commercial entity could improve its productivity and become more competitive if it better manages its income.